Supplementary figures file from Multiple-batch spawning: a risk-spreading strategy disarmed by highly intensive size-selective fishing rate - Sara Hočevar; Jeffrey A. Hutchings; Anna Kuparinen (2022)
Eight figures illustrating further eco-evolutionary characteristics of multiple-batch spawning strategy.